Alienation and nostalgia as an outlet for the patriotic and national poetry of the poet Al-Kazemi (Journal of the College of Basic Education, 2023)
The issue of estrangement and what it reflects of revelations and pressures is not a psychological illusion on the poet.The Arabic is new, so the alienation and the nostalgia associated with it have accompanied the march of Arab poetry since its most ancient times.But what is new in our vision of alienation is that it be a real deterrent and clear to another poetic issue whose presence wasThe beginning of the last century, an active presence of the well-known political conditions that the country is going throughThe Arab is suffering under the yoke of various types of Ottoman and Western colonialism.National and national poetic.